2020
DOI: 10.15414/afz.2020.23.03.117-124
|View full text |Cite
|
Sign up to set email alerts
|

Differences in soil organic matter and humus of sandy soil after application of biochar substrates and combination of biochar substrates with mineral fertilizers

Abstract: The effort to achieve the sustainable farming system in arable soil led to the intensive search for a new solution but an inspiration can also be found in the application of traditional methods of soil fertility improvement as it is shown in numerous examples in history. Recently many scientific teams have focused their attention on the evaluation of biochar effects on soil properties and crop yields. Since there are a lot of knowledge gaps, especially in explanations how biochar can affect soil organic matter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…For this reason, little is known about its effects on the speed of humification and the creation of humic substances or their stabilisation in the soils. Several authors have stated that biochar application holds significant potential for forming and stabilising soil humic substances [27,28,[55][56][57][58][59][60]-a conclusion supported by our research, but only in the case of both biochar doses combined with the second level of nitrogen fertilisation (Table 3). However, if it is applied at a dose of 10 or 20 t ha −1 alone, or in combination with the lower level of N fertilisation, to Haplic Luvisols in a mild climate, it has no significant effect on the humic substances in the soil.…”
Section: Effects Of Biochar On Humic Substancessupporting
confidence: 81%
“…For this reason, little is known about its effects on the speed of humification and the creation of humic substances or their stabilisation in the soils. Several authors have stated that biochar application holds significant potential for forming and stabilising soil humic substances [27,28,[55][56][57][58][59][60]-a conclusion supported by our research, but only in the case of both biochar doses combined with the second level of nitrogen fertilisation (Table 3). However, if it is applied at a dose of 10 or 20 t ha −1 alone, or in combination with the lower level of N fertilisation, to Haplic Luvisols in a mild climate, it has no significant effect on the humic substances in the soil.…”
Section: Effects Of Biochar On Humic Substancessupporting
confidence: 81%
“…As indicated by several recent studies (Bai et al, 2022;Balashov et al, 2021;Głąb et al, 2016;He et al, 2022;Horák et al, 2020;Igaz et al, 2018;Juriga et al, 2021;Saravanan and Kumar, 2022;Šimanský et al, 2018), biochar is considered a promising agronomic tool for modifying soil properties. However, different effects of various biochars on soils were recorded (Bai et al, 2022;El-Naggar et al, 2019;Horák et al, 2020;Hossain et al, 2020;Šimanský et al, 2022;Šrank and Šimanský, 2020). Biochar application to soils can cause both a positive and a negative priming effect, and depending on this effect, an increase or decrease in SOC will be observed.…”
Section: Effect Of Biochar Application and Nitrogen Fertilisation On ...mentioning
confidence: 99%
“…Biochar can be an excellent agronomic as well as an environmental tool for increasing SOM content and for mitigating the flux of CO2 from arable land into the atmosphere (Balashov et al, 2021;He et al, 2022;Juriga et al, 2021;Saravanan and Kumar, 2022;Šimanský et al, 2018). Biochar is a significant source of stable organic C (Fisher and Glaser, 2012;Šrank and Šimanský, 2020). After biochar application, as a rule, the entire complex of chemical, physical and biological properties of soils changes (Balashov et al, 2022;Juriga et al, 2021;Šimanský et al, 2022;Zheng et al, 2022), which also can result in higher yields of cultivated crops (Bai et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of high chemical stability, biochar has a great potential to enhance atmospheric carbon sequestration (Laird et al, 2008;Lehmann et al, 2006). Soil amendments such as biochar, composts or their mixtures can decrease soil bulk density (Abd El-Mageed et al, 2021;Hardie et al, 2014), improve soil structure (Ajayi and Horn, 2016;Juriga et al, 2021), increase soil pH (Horák, 2015) cation exchange capacity (Igaz et al, 2018;Jien and Wang, 2013), soil N availability (Haider et al, 2017;Van Zwieten et al, 2010), organic carbon content (Ajayi and Horn, 2016;Šrank and Šimanský, 2020), soil porosity (Blanco-Canqui, 2017;Githinji, 2014), available water content (Głąb et al, 2016;Ibrahim et al, 2013) and saturated hydraulic conductivity (Jien and Wang, 2013;Toková et al, 2020). Syakila and Kroeze (2011) reported that agricultural N2O emission in 2006 reached 23-31% of the global emissions with the main source being nitrogen fertilizer and manure application to soils.…”
Section: Introductionmentioning
confidence: 99%